Performance Analysis Of Power Optimization Over (32channels×40Gb/s) Based On Optical Network - Essa Ibrahim Essa; Mshari Aead Asker (Al-Qadisiyah Journal of Pure Science, 2018)
The input power of an optical transmitter is an important key in WDM networks; therefore these leads to a good output signal at the receiver side. In this article, the (32Channel×40Gbps) total of (1.2Tbps) of bandwidth done in a series of computer simulations, with NRZ modulation format over SSMF link with length is (50km), and power optimization are investigated, and their performances. The (BER = 6.1548× ), the average optical power level for all channels is (-26.6449dBm) while the average maximum Q-factors for all 32-channels are (5.2669). The best power for our simulation is (2.5118mW).The Kerr effects on WDM networks that were taken into account, also, the dispersion compensation fiber (DCF) are used to compensating the dispersion and the power loss are substituted by Erbium-doped fiber amplifier (EDFA). The simulation results show that data transmission rates are successfully transmitted with low-cost effective infrastructure with good system performance, and minimizing the probability of error for the whole network is of interest, and the system performance is well in the whole network. Our simulation designed, simulated, tested, and verified by Optisystem package is a license product Canadian company.